PERBEDAAN METODE DRILL DAN METODE INKUIRI TERHADAP EFEKTIFITAS HASIL BELAJAR PASSING BAWAH PERMAINAN BOLA VOLI SISWA KELAS IX SMP NEGERI 4 AIR SALEK - Sandi Nurhuda; Henki Kumbara; Daryono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The effectiveness of learning outcomes in the passing technique between the use of the drill method and the inquiry method in teaching volleyball to ninth-grade students at SMP Negeri 4 Air Salek. The research problem formulation is: How do the Drill Method and the Inquiry Method Influence the Effectiveness of Learning Outcomes in Passing Techniques in Volleyball at SMP Negeri 4 Air Salek? The aim of this research is to determine the influence and differences between the use of the Drill and Inquiry methods. The research method employed is an experimental method. Data collection techniques include observation, interviews, and documentation. Data analysis employs the t-test. The research findings indicate the influence of the drill method on passing technique learning outcomes, as the t-value of 11.129 > the t-table value of 1.833, with a contribution of 94.6%. Additionally, the inquiry method has an influence on passing technique learning outcomes, with a t-value of 6.332 > the t-table value of 1.833, with a contribution of 60.7%. Furthermore, there is a difference before and after applying the drill and inquiry methods to passing technique learning outcomes among students at SMP Negeri 4 Air Salek, as the F-value of 4.480 > the F-table value of 3.55.